Effective sound therapy using a hearing aid and educational counseling in patients with chronic tinnitus. Issue 5 (October 2021) - Shinden, Seiichi; Suzuki, Noriomi; Oishi, Naoki; Suzuki, Daisuke; Minami, Shujiro; Ogawa, Kaoru
Abstract: Objective: This study aimed to assess the effectiveness of our sound therapy with appropriate hearing aid fitting and periodic hearing aid adjustment in patients with chronic tinnitus. Methods: We conducted a retrospective study. The study included 490 individuals who received treatment with hearing aids for chronic tinnitus at least for 3 months. To determine the effects of tinnitus on patients' quality of life, the participants completed a series of questionnaires, including the Tinnitus Handicap Inventory (THI), Visual Analogue Scale (VAS) for loudness and annoyance, and questionnaires of subjective symptom improvement. Data were collected at entry and 3 months and 1 year after treatment initiation. Results: All 490 participants completed the questionnaires at 3 months; however, only 312 completed them at 1 year. The mean ± standard deviation THI score before treatment decreased significantly at 3 months (490 participants: 53 ± 25 to 11 ± 16 and 312 participants: 55 ± 24 to 12 ± 16) and 1 year (55 ± 24 to 9 ± 14) ( P < 0.01). The mean VAS score for tinnitus loudness before treatment decreased significantly at 3 months (490 participants: 70 ± 22 to 25 ± 27 and 312 participants: 71 ± 22 to 27 ± 26) and 1 year (71 ± 22 to 21 ± 28) ( P < 0.01). In addition, the mean VAS score for tinnitus annoyance before treatment decreased significantly at 3 months (490 participants: 75 ± 26 to 20 ± 26 and 312 participants: 75 ± 25 to 23 ± 27) and 1 year (75 ± 25 to 17 ± 26) ( P < 0.01). Approximately 80% of patients noticed improvements in their tinnitus annoyance and loudness, as determined by their responses to the questionnaires of subjective symptom improvement. Conclusion: The results of this study suggest that treatment with sound therapy may ameliorate the symptoms of chronic tinnitus associated with hearing loss.